2017
DOI: 10.1097/scs.0000000000004049
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effects of the Use of Propofol in Experimental Model Inferior Epigastric Island Flap on Ischemia-Reperfusion Injury

Abstract: Problems concerning vascular blood flow are the most frequently encountered ones after flap applications. The flap tissue starts to develop ischemia in patients with a vascular blood flow insufficiency. And reperfusion starts in those patients in whom the ischemia is temporary, triggering an ischemia-reperfusion injury depending on the duration of the ischemia. The aim of this study was to evaluate the effect of propofol, which is an anesthetic agent known to have an antioxidant effect and a free radical scave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In the present study, HE staining of IRI-affected rat renal tissue (Fig. 1) and biochemical tests of intravenous blood ( Table 1) have confirmed that propofol has a protective effect against renal IRI, which is consistent with what other researchers have found [35]. Although the protective mechanism of propofol against renal ischemia-reperfusion is not fully clear, there have been studies suggesting that the gap junction protein Cx43 may be involved in the role of propofol [13,29,32,36].…”
Section: +supporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, HE staining of IRI-affected rat renal tissue (Fig. 1) and biochemical tests of intravenous blood ( Table 1) have confirmed that propofol has a protective effect against renal IRI, which is consistent with what other researchers have found [35]. Although the protective mechanism of propofol against renal ischemia-reperfusion is not fully clear, there have been studies suggesting that the gap junction protein Cx43 may be involved in the role of propofol [13,29,32,36].…”
Section: +supporting
confidence: 80%
“…It has also been found by multiple research teams that propofol has protective effects against IRI in multiple organs [33,34]. Propofol infusion has also been suggested to have protective effects against renal IRI in rats, but the underlying mechanism is not fully understood [10,13,35]. In the present study, HE staining of IRI-affected rat renal tissue (Fig.…”
Section: +mentioning
confidence: 68%
“…Due to this, the scope of application in this study may be limited (19). The patients included in this study were mainly middle-aged and elderly patients, and propofol was used for anesthesia during hepatectomy of the hepatic port block (20). Therefore, there may be a clear distinction between minors and patients who have not undergone hepatectomy under anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…As an important inflammatory cytokine, TNF-α mainly produced by the activation of monocytes/macrophages is involved in certain autoimmune diseases (Liu et al, 2019). Therefore, it can stimulate NO synthase (i-NOS) synthesis to release large amounts of NO (Eroglu et al, 2017). This will exacerbate peroxidation of membrane lipid and tissue damage.…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%